2018
DOI: 10.1083/jcb.201606055
|View full text |Cite
|
Sign up to set email alerts
|

The Cullin-3–Rbx1–KCTD10 complex controls endothelial barrier function via K63 ubiquitination of RhoB

Abstract: The RhoA GTPase controls endothelial cell migration, adhesion, and barrier formation but the role of RhoB is unclear. Kovačević et al. now discover that RhoB is ubiquitinated by the CUL3–Rbx1–KCTD10 complex and that this is a prerequisite for lysosomal degradation of RhoB and the maintenance of endothelial barrier integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 70 publications
3
81
0
Order By: Relevance
“…An inhibitory role of RhoB in endothelial barrier formation was also implicated in TNF‐simulated HUVEC and vascular endothelial cells in Crohn('s disease . Mechanistically, we found that RhoB was constitutively degraded in lysosomes, and the degradation process was mediated through K63 polyubiquitination at lysine 162 and 181 of RhoB by CUL3/KCTD10 …”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…An inhibitory role of RhoB in endothelial barrier formation was also implicated in TNF‐simulated HUVEC and vascular endothelial cells in Crohn('s disease . Mechanistically, we found that RhoB was constitutively degraded in lysosomes, and the degradation process was mediated through K63 polyubiquitination at lysine 162 and 181 of RhoB by CUL3/KCTD10 …”
Section: Introductionmentioning
confidence: 69%
“…Interestingly, the translocation of Rac1 was inhibited by high expression of RhoB, resulting in impaired barrier restoration . Given our finding of the constitutive degradation of RhoB by CUL3/KCTD10, CUL3/KCTD10 may be critical for Rac1 trafficking and activation through RhoB degradation.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…In endothelial cells, RhoB half‐life is regulated by polyubiquitination at lysines 162 and 181 (Kovačević et al, ), therefore we generated BECs stably expressing Myc‐tagged RhoB K162R/K181R and assessed RhoB expression on soft substrates. Although RhoB K162R/K181R was generally expressed at lower levels than wild‐type even on plastic, seeding these cells on gels further reduced RhoB expression suggesting that ubiquitination was not required for RhoB downregulation (Figure b).…”
Section: Resultsmentioning
confidence: 99%